Трохикола энтерикус - Trochicola entericus Dollf. (Copepoda, Mytilicolidae) - паразит моллюсков Черного моря - Долгих, А.В.; Сажина, Л.И. (Вестник зоологии, 1968)
Parasitic Trochicola entericus Dollf. were found for the first time in the Black Sea mollusks Tricolia pulla (L.) (from the regions of Sevastopol, Karadag, Novorossiisk and. Tuapse) and in Gibbulla divaricata (L.) (from the Sevastopol region). Females were localized in bowels, and males and copepodites — in gill cavities of the mollusks. The dimensions of Trochicola entericus Doll f. are somewhat less that those described by other authors. The extensiveness of mollusk invasion surpasses 50%.